2012
DOI: 10.1111/j.1360-0443.2012.04015.x
|View full text |Cite
|
Sign up to set email alerts
|

The persistence of the association between adolescent cannabis use and common mental disorders into young adulthood

Abstract: Regular (particularly daily) adolescent cannabis use is associated consistently with anxiety, but not depressive disorder, in adolescence and late young adulthood, even among regular users who then cease using the drug. It is possible that early cannabis exposure causes enduring mental health risks in the general cannabis-using adolescent population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
160
2
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(177 citation statements)
references
References 34 publications
9
160
2
6
Order By: Relevance
“…However, a 10-year longitudinal study in Germany demonstrated that mood and anxiety disorders, as well as the degree of their comorbidity, were significantly associated with the incidence of cannabis use and the progression to cannabis use disorders, even when controlling for externalizing disorders (Wittchen et al, 2007). Similarly, a 15-year longitudinal study in Australia demonstrated that after controlling for multiple potential confounds, regular (particularly daily) adolescent cannabis use was associated consistently with anxiety disorder, but not depressive disorder, in adolescence and late young adulthood, even among users who then ceased cannabis use (Degenhardt et al, 2013). Additionally, a study using data from the NESARC reported that social anxiety disorder was more likely to be related to cannabis dependence than abuse, and that this relation remained significant after controlling for race, sex, and other substance use and psychiatric disorders; this study also reported that in the majority of cases, but not all cases, the development of social anxiety disorder preceded the development of cannabis use disorders (Buckner et al, 2012b).…”
Section: June 2007 Using International Classification Of Diseases (Imentioning
confidence: 94%
“…However, a 10-year longitudinal study in Germany demonstrated that mood and anxiety disorders, as well as the degree of their comorbidity, were significantly associated with the incidence of cannabis use and the progression to cannabis use disorders, even when controlling for externalizing disorders (Wittchen et al, 2007). Similarly, a 15-year longitudinal study in Australia demonstrated that after controlling for multiple potential confounds, regular (particularly daily) adolescent cannabis use was associated consistently with anxiety disorder, but not depressive disorder, in adolescence and late young adulthood, even among users who then ceased cannabis use (Degenhardt et al, 2013). Additionally, a study using data from the NESARC reported that social anxiety disorder was more likely to be related to cannabis dependence than abuse, and that this relation remained significant after controlling for race, sex, and other substance use and psychiatric disorders; this study also reported that in the majority of cases, but not all cases, the development of social anxiety disorder preceded the development of cannabis use disorders (Buckner et al, 2012b).…”
Section: June 2007 Using International Classification Of Diseases (Imentioning
confidence: 94%
“…Both frequent (daily or nearly daily) cannabis use and cannabis dependence are associated with various mental health problems [1][2][3][4][5][6][7]. However, in most studies the overlap (an estimated 20-50% [8,9]) between dependent users and frequent users is ignored [1][2][3][4][5][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…These studies show higher rates of depression and anxiety in dependent versus non-dependent users and in heavy versus infrequent users [3,6,[10][11][12][13][14][15][16]. However, other studies found similar rates of internalizing disorders in heavy and infrequent users [6,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the total population of India, the number of users will be around an alarming estimate of 50 Lakhs. It is reported that many of opioid dependent patients also are reported to be sufferers of illnesses like HIV, Hepatitis B and C. 1 Opioid use disorders are progressively increasing cause of deaths too. Opioid use disorders resulted in 51,000 deaths worldwide in 2013 where as it was estimated to be 18,000 deaths in 1990.…”
Section: Introductionmentioning
confidence: 99%